Negative pole piece, battery and energy storage device

By reasonably proportioning and distributing hard carbon materials in the active material layer of the negative electrode sheet, the problem that hard carbon materials are difficult to obtain high capacity and high compaction density at the same time is solved, and the volume energy density and cycle stability of the battery are improved.

CN119252859AActive Publication Date: 2025-01-03XIAMEN HITHIUM ENERGY STORAGE TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411388371.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Hard carbon materials are difficult to obtain high capacity and high compaction density at the same time, resulting in a decrease in the volume energy density of the battery, limiting its industrial application in battery products.

Method used

By using the first hard carbon material and the second hard carbon material in the active material layer of the negative electrode sheet, the particle size distribution characteristics and cross-sectional area ratio are controlled, and combined with the specific porosity, the stacking method of hard carbon materials is optimized to increase pressure Real density.

Benefits of technology

Without affecting the capacity performance of hard carbon materials, the compaction density of the negative electrode sheet is significantly improved, thereby improving the volume energy density and cycle stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252859A_ABST
    Figure CN119252859A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a negative pole piece, a battery and an energy storage device. The negative pole piece comprises a current collector; the active material layer is arranged on the current collector; the active material layer comprises a first hard carbon material and a second hard carbon material, the Dv50 of the first hard carbon material is 4 [mu] m-7 [mu] m, the Dv50 of the second hard carbon material is smaller than the Dv50 of the first hard carbon material, and the first hard carbon material accounts for 15%-45% of the cross-sectional area of the active material layer; and the porosity of the negative pole piece is 1%-10%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode plate, a battery and an energy storage device. Background Art

[0002] Hard carbon material is an electrode material with good application prospects and can be used as anode material of batteries. However, due to the material properties of the precursors used to prepare hard carbon materials, it is difficult for hard carbon materials to obtain high capacity and compaction density at the same time. Summary of the invention

[0003] In order to solve the above technical problems, the present invention discloses a negative electrode plate and a preparation method thereof, and an energy storage device, which improve the compaction density of hard carbon materials without affecting the capacity advantage of hard carbon materials, thereby improving the volume energy density of the battery and optimizing battery performance.

[0004] In a first aspect, the present application provides a negative electrode plate, the negative electrode plate comprising:

[0005] current collector;

[0006] An active material layer is disposed on the current collector; the active material layer comprises a first hard carbon material and a second hard carbon material, the Dv50 of the first hard carbon material is 4 μm to 7 μm, the Dv50 of the second hard carbon material is less than the Dv50 of the first hard carbon material, and the cross-sectional area of ​​the first hard carbon material in the active material layer accounts for 15% to 45%;

[0007] The porosity of the negative electrode plate is 1% to 10%.

[0008] Furthermore, the first hard carbon material is at least one of spherical or quasi-spherical particles, the second hard carbon material is three-dimensional geometric block particles, and the Dv50 of the second hard carbon material is less than 4 μm.

[0009] Furthermore, the average shape factor F of the first hard carbon material is ≥ 0.75, and the average shape factor F = 4πA / P 2 , wherein A is the cross-sectional area of ​​the first hard carbon material, and P is the cross-sectional perimeter of the first hard carbon material.

[0010] Further, in terms of mass percentage, the hard carbon material includes 60 wt% to 80 wt% of the first hard carbon material and 20 wt% to 40 wt% of the second hard carbon material; wherein the Dv50 of the second hard carbon material is 1.5 μm to 3 μm.

[0011] Furthermore, the hard carbon material further comprises a third hard carbon material, the third hard carbon material is a spherical or quasi-spherical particle, and the Dv50 of the third hard carbon material is 2 μm to 4 μm;

[0012] The Dv50 of the second hard carbon material is less than or equal to 2 μm;

[0013] In terms of mass percentage, the hard carbon material includes 65 wt % to 75 wt % of the first hard carbon material, 10 wt % to 30 wt % of the second hard carbon material, and 5 wt % to 15 wt % of the third hard carbon material.

[0014] Furthermore, Dn10 of the first hard carbon material is 0.3 μm to 0.5 μm.

[0015] Furthermore, Dn10 of the second hard carbon material is 0.3 μm to 0.5 μm.

[0016] Furthermore, Dn10 of the third hard carbon material is 0.45 μm to 0.55 μm.

[0017] Further, the porosity of the negative electrode plate is 4% to 6%; and / or,

[0018] The compaction density of the negative electrode plate is greater than or equal to 0.98 g / cm 3 .

[0019] Furthermore, the first hard carbon material and the second hard carbon material are respectively prepared from precursors, and the precursors include one or more of a biomass-based precursor, a resin-based precursor, a pitch-based precursor, and a coal-based precursor.

[0020] In the second aspect, the present application provides a battery, comprising: a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the separator is arranged between the positive electrode plate and the negative electrode plate to form a battery cell, and the electrolyte is injected into the battery cell, wherein the negative electrode plate is the negative electrode plate as described in the first aspect.

[0021] In a third aspect, the present application provides an energy storage device, which includes the negative electrode plate as described in the first aspect, or the energy storage device includes the battery as described in the second aspect.

[0022] Compared with the prior art, the beneficial effects of this application are as follows:

[0023] Through in-depth research on the particle size distribution characteristics of hard carbon materials, the proportion of their cross-sectional area in the active material layer, and the corresponding porosity of the negative electrode sheet, the present application creatively discovered that when a first hard carbon material with a Dv50 of 4μm to 7μm is used as the main active material in the active material layer, its cross-sectional area proportion in the active material layer is controlled within the range of 15% to 45% and the corresponding negative electrode sheet porosity is 1% to 10%, the negative electrode sheet can have a higher compaction density without affecting the capacity performance of the hard carbon material itself. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 It is a schematic diagram of the structure of the negative electrode sheet of an embodiment of the present application;

[0026] Figure 2 yes Figure 1 A magnified schematic diagram of the structure at center A;

[0027] Figure 3 is a schematic diagram corresponding to the method for measuring the first hard carbon material in an embodiment of the present application;

[0028] Figure 4 is a schematic diagram corresponding to the method for measuring the second hard carbon material in the embodiment of the present application;

[0029] Figure 5 is a structural schematic diagram of a household energy storage system according to an embodiment of the present application;

[0030] Figure 6 It is a structural schematic diagram of an energy storage system according to an embodiment of the present application.

[0031] Figure numerals: 1. current collector; 2. active material layer; 21. first hard carbon material; 22. second hard carbon material; 100. energy storage system; 10. energy storage device; 20. electric energy conversion device; 30. first user load; 40. second user load; 50. high-voltage cable; 60. first electric energy conversion device; 70. second electric energy conversion device. DETAILED DESCRIPTION

[0032] In the present invention, the directions or positional relationships indicated by the terms "upper", "lower", "left", "right", "front", "back", "top", "bottom", "inner", "outer", "middle", "vertical", "horizontal", "lateral", "longitudinal" and the like are based on the directions or positional relationships shown in the drawings. These terms are mainly used to better describe the present invention and its embodiments, and are not used to limit the indicated devices, elements or components to have a specific direction, or to be constructed and operated in a specific direction.

[0033] In addition, some of the above terms may be used to express other meanings in addition to indicating a direction or position relationship. For example, the term "on" may also be used to express a certain dependency or connection relationship in some cases. For those of ordinary skill in the art, the specific meanings of these terms in the present invention can be understood according to specific circumstances.

[0034] In addition, the terms "installed", "set", "provided with", "connected", and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral structure; it can be a mechanical connection, or an electrical connection; it can be a direct connection, or an indirect connection through an intermediate medium, or it can be an internal connection between two devices, elements, or components. For those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0035] In addition, the terms "first", "second", etc. are mainly used to distinguish different devices, elements or components (the specific types and structures may be the same or different), and are not used to indicate or imply the relative importance and quantity of the indicated devices, elements or components. Unless otherwise specified, "plurality" means two or more.

[0036] Hard carbon materials have the advantages of a wide range of material sources and better low-temperature rate performance, and are suitable for use as negative electrode active materials for batteries (such as lithium-ion batteries, sodium-ion batteries, etc.). However, due to the different properties of various precursor materials used to prepare hard carbon materials, it is often difficult for hard carbon materials to have both excellent capacity performance and compaction density. Hard carbon materials prepared from some precursors have the characteristics of low capacity but high compaction density; hard carbon materials prepared from other precursors have the characteristics of high capacity but low compaction density. It can be seen that if you want to maintain the high capacity advantage of hard carbon materials, it is difficult to obtain a higher compaction density level, which in turn leads to a decrease in the volume energy density of the battery, which is not conducive to the industrial application of hard carbon materials in battery products.

[0037] In response to the above problems, the embodiments of the present application provide a negative electrode plate, a battery and an energy storage device, which can effectively improve the compaction density of the negative electrode plate without affecting the capacity performance of the hard carbon material, thereby improving the volume energy density of the battery and optimizing the battery performance.

[0038] The first aspect is combining Figure 1 and Figure 2 As shown, Figure 1 : is a schematic diagram of the structure of the negative electrode sheet of the embodiment of the present application, wherein part of the internal materials of the active material layer 2 are shown for the convenience of understanding the technical solution of the embodiment of the present application; Figure 2 yes Figure 1 An enlarged schematic diagram of the structure at A in the figure. The embodiment of the present application provides a negative electrode plate, comprising a current collector 1 and an active material layer 2 disposed on the current collector 1. The active material layer 2 comprises a first hard carbon material 21 and a second hard carbon material 22 as active materials, the Dv50 of the first hard carbon material 21 is 4 μm to 7 μm, the Dv50 of the second hard carbon material 22 is less than the Dv50 of the first hard carbon material 21, the cross-sectional area of ​​the first hard carbon material 21 in the active material layer 2 accounts for 15% to 45%, and the porosity of the negative electrode plate is 1% to 10%.

[0039] It is understandable that hard carbon materials are active materials that can reversibly embed and deintercalate lithium ions (or sodium ions, etc.) and can directly participate in electrochemical reactions. Therefore, in the embodiment of the present application, the active material layer 2 includes a first hard carbon material 21 and a second hard carbon material 22, which means that these hard carbon materials are the main components of the active material layer 2. However, in addition to hard carbon materials, the active material layer 2 may also include other additives such as binders, conductive agents, dispersants, etc. in conventional amounts. Compared with hard carbon materials, these additives have a lower effect on the compaction density of the negative electrode sheet, so the present application does not limit these additives. In addition, the active material layer 2 can be set on one side or both sides of the current collector 1.

[0040] In addition, the Dv50 of the first hard carbon material 21 is 4 μm to 7 μm, including any point value within the numerical range, for example, the Dv50 of the first hard carbon material 21 is 4 μm, 5 μm, 6 μm or 7 μm. The cross-sectional area of ​​the first hard carbon material 21 in the active material layer 2 accounts for 15% to 45%, including any point value within the numerical range, for example, the cross-sectional area of ​​the first hard carbon material 21 in the active material layer 2 accounts for 15%, 20%, 25%, 30%, 35%, 40% or 45%. The porosity of the negative electrode sheet is 1% to 10%, including any point value within the numerical range, for example, the porosity of the negative electrode sheet is 1%, 2%, 3%, 5%, 8% or 10%.

[0041] Through in-depth research on the particle size distribution characteristics of hard carbon materials, the proportion of their cross-sectional area in the active material layer 2, and the corresponding porosity of the negative electrode sheet, the present application creatively discovered that when the first hard carbon material 21 with a Dv50 of 4μm to 7μm is used as the main active material in the active material layer 2, and its cross-sectional area proportion in the active material layer 2 is controlled within the range of 15% to 45% and the corresponding negative electrode sheet porosity is 1% to 10%, the negative electrode sheet can have a higher compaction density without affecting the capacity performance of the hard carbon material itself.

[0042] The particle size distribution characteristics of the hard carbon materials, their cross-sectional area ratio in the active material layer 2, and the porosity of the negative electrode sheet have important and close influences on optimizing the densest stacking mode of the hard carbon materials in the active material layer 2 and the utilization degree of the gap space formed between adjacent active materials. According to the fact that the first hard carbon material 21 with a Dv50 of 4μm to 7μm in the active material layer 2 accounts for 15% to 45% of the cross-sectional area in the active material layer 2, and the Dv50 of the second hard carbon material 22 is even smaller, it can be seen that the first hard carbon material 21 with a relatively large size plays a leading role in the active material layer 2. First, it exerts its capacity performance based on the properties of the first hard carbon material 21, and second, it is effectively stacked as large-sized particles to be distributed in the active material layer 2 at a certain density.

[0043] At the same time, because the Dv50 of the second hard carbon material 22 is smaller, and the porosity of the negative electrode plate is 1% to 10%, the densest stacking mode of the hard carbon material in the active material layer 2 is: the large-sized particles of the first hard carbon material 21 are stacked to form a certain gap space, and the small-sized second hard carbon material 22 is stacked in these gap spaces, thereby improving the utilization of the gap space, optimizing the densest stacking mode, and thus improving the compaction density. In addition, although the Dv50 of the first hard carbon material 21 is greater than that of the second hard carbon material 22, the level of the Dv50 of the first hard carbon material 21 is 4μm to 7μm, which is less than 10μm. It is still a particle with a relatively small particle size as a whole, so it can better fill the active material layer 2 and improve the compaction density.

[0044] It can be seen that the embodiment of the present application can not only utilize the first hard carbon material 21 with a Dv50 of 4μm to 7μm within a specific proportion range to exert the capacity performance of the material itself through the cooperation of the above factors, but also can fill the second hard carbon material 22 into the gap space between the first hard carbon material 21 through the cooperation between the second hard carbon material 22 and the first hard carbon material 21 with specific cross-sectional proportion and particle size distribution characteristics, thereby improving the space utilization of the active material layer 2. In addition, the second hard carbon material 22 also provides a shorter channel for the embedding and extraction of lithium ions (or sodium ions) due to its smaller particles, which is conducive to further improving the dynamic performance of the battery.

[0045] Furthermore, the first hard carbon material 21 is at least one of spherical particles or quasi-spherical particles, the second hard carbon material 22 is a three-dimensional geometric block particle, and the Dv50 of the second hard carbon material 22 is less than 4 μm.

[0046] When the first hard carbon material 21 is a spherical particle, the spherical particle refers to a particle that is approximately spherical in shape, for example, the spherical particle may be an ellipsoidal particle, an irregular pebble-shaped particle, etc. When the equivalent diameter of these spherical particles is measured using a scanning electron microscope, the one-dimensional width of the spherical particles can be measured in different directions, and then the average of the measured multiple one-dimensional widths is calculated to obtain the equivalent diameter. Figure 3 As shown, the one-dimensional width of the spherical particles is measured in the first direction to obtain the first one-dimensional width x1, and the one-dimensional width of the spherical particles is measured in the second direction to obtain the second one-dimensional width x2. The average of x1 and x2 is calculated to obtain the equivalent diameter x.

[0047] The second hard carbon material 22 is a three-dimensional geometric block particle, which refers to a block particle composed of multiple polygons or composed of polygons and curved surfaces. This type of block particle has more edges and planes because its outer surface has polygons. For example, the three-dimensional geometric block particles can be regular or irregular cubes, hexahedrons, octahedrons or pyramids, etc. When using a scanning electron microscope to measure the equivalent diameter of these three-dimensional geometric block particles, the one-dimensional width of the three-dimensional geometric block particles can be measured in different directions, and then the average of the multiple one-dimensional widths measured can be calculated to obtain the equivalent diameter. For example Figure 4 As shown, the one-dimensional width of the three-dimensional geometric block particles is measured in the first direction to obtain the first one-dimensional width y1, and the one-dimensional width of the three-dimensional geometric block particles is measured in the second direction to obtain the second one-dimensional width y2. The average of y1 and y2 is calculated to obtain the equivalent diameter y.

[0048] For example, in an optional embodiment, the first hard carbon material 21 includes both spherical particles and quasi-spherical particles; the second hard carbon material 22 includes irregular cube, hexahedron, octahedron and other three-dimensional geometric block particles. In another optional embodiment, the first hard carbon material 21 is quasi-spherical particles, and the second hard carbon material 22 includes irregular cube, hexahedron and other three-dimensional geometric block particles.

[0049] Since the first hard carbon material 21 is spherical or quasi-spherical, the gap space formed between adjacent first hard carbon materials 21 often has the spatial shape characteristics of a large space in the middle and a narrow gap at the edge. Since the second hard carbon material 22 with a smaller Dv50 is a block particle of a three-dimensional geometry, it has more edges and angles adapted to the narrow and long space. Therefore, these three-dimensional geometric block particles have a higher matching degree with the gap space of the adjacent first hard carbon material 21, and can fill more narrow gaps, so that the pores of the negative electrode plate are less and the compaction density is higher. At the same time, since the contact between the spherical or quasi-spherical first hard carbon material 21 and the three-dimensional geometric block particles is mostly a point-to-plane contact mode, it is more stable than the point-to-point contact mode between spherical large-sized particles and spherical small-sized particles, which is conducive to maintaining the structural stability of the active material layer 2 during the processing process and reducing the problems of misalignment and deformation of the first hard carbon material 21 and the second hard carbon material 22 caused by processing conditions (such as applying pressure to the active material layer 2).

[0050] Furthermore, the average shape factor F of the first hard carbon material 21 is ≥ 0.75, and the average shape factor F = 4πA / P 2 , wherein A is the cross-sectional area of ​​the first hard carbon material 21, and P is the cross-sectional perimeter of the first hard carbon material 21. Exemplarily, F is 0.75, 0.80, 0.85, 0.90, 0.95, 0.99 or 1. A higher average shape factor indicates that the first hard carbon material 21 is closer to a sphere, has better isotropy, and has better particle structure stability, which is conducive to further improving the structural stability of the negative electrode sheet during processing.

[0051] The longitudinal cross-sectional area of ​​the first hard carbon material along the thickness direction of the active material layer is measured and calculated, and the transverse cross-sectional area of ​​the first hard carbon material along the thickness direction perpendicular to the active material layer is measured and calculated, and the longitudinal cross-sectional area and the transverse cross-sectional area are averaged to obtain the cross-sectional area. The longitudinal cross-sectional perimeter of the first hard carbon material along the thickness direction of the active material layer is measured and calculated, and the transverse cross-sectional perimeter of the first hard carbon material along the thickness direction perpendicular to the active material layer is measured and calculated, and the longitudinal cross-sectional perimeter and the transverse cross-sectional perimeter are averaged to obtain the cross-sectional perimeter.

[0052] In an optional embodiment, the hard carbon material includes 60wt% to 80wt% of the first hard carbon material 21 and 20wt% to 40wt% of the second hard carbon material 22 in terms of mass percentage; wherein the Dv50 of the second hard carbon material 22 is 1.5μm to 3μm. For example, the hard carbon material includes 60wt% of the first hard carbon material 21 and 40wt% of the second hard carbon material 22, or the hard carbon material includes 70wt% of the first hard carbon material 21 and 30wt% of the second hard carbon material 22, or the hard carbon material includes 75wt% of the first hard carbon material 21 and 25wt% of the second hard carbon material 22. In addition, the Dv50 of the second hard carbon material 22 is 1.5μm to 3μm, including any point value within the numerical range, for example, the Dv50 of the second hard carbon material 22 is 1.5μm, 1.8μm, 2.0μm, 2.2μm, 2.5μm, 2.8μm or 3.0μm.

[0053] In the embodiment of the present application, the usage ratio of the first hard carbon material 21 with a Dv50 of 4μm to 7μm is higher than the usage ratio of the second hard carbon material 22 with a Dv50 of 1.5μm to 3μm. On the one hand, whether it is the first hard carbon material 21 with a relatively large particle size or the second hard carbon material 22 with a relatively small particle size, the overall particle size of the two is less than 10μm. It can be seen that the hard carbon material in the active material layer 2 of the embodiment of the present application generally adopts small-particle hard carbon materials to better improve the compaction density; especially the particle size of the second hard carbon material 22 is less than or equal to 3μm, and the three-dimensional geometric block particles in this particle size range help to more significantly improve the compaction density. On the other hand, the spherical or quasi-spherical first hard carbon material 21 is used in larger amounts than the three-dimensional geometric block-shaped second hard carbon material 22, indicating that the active material layer 2 as a whole still uses the first hard carbon material 21 with better isotropy as the main hard carbon material component, and the second hard carbon material 22 with better anisotropy is filled in the gap space of the first hard carbon material 21, which does not affect the capacity performance of the negative electrode plate, maintains better structural stability, and provides better compaction density.

[0054] In another optional embodiment, the hard carbon material further includes a third hard carbon material, the third hard carbon material is a spherical or quasi-spherical particle, the Dv50 of the third hard carbon material is 2 μm to 4 μm, and the Dv50 of the second hard carbon material 22 is less than or equal to 2 μm. In terms of mass percentage, the hard carbon material includes 65 wt% to 75 wt% of the first hard carbon material 21, 10 wt% to 30 wt% of the second hard carbon material 22, and 5 wt% to 15 wt% of the third hard carbon material.

[0055] Among them, the Dv50 of the third hard carbon material is 2μm to 4μm, including any point value within the numerical range, for example, the Dv50 of the third hard carbon material is 2μm, 2.5μm, 3μm, 3.5μm or 4μm. The Dv50 of the second hard carbon material 22 is less than or equal to 2μm, including any point value within the numerical range, for example, the Dv50 of the second hard carbon material 22 is 1μm, 1.2μm, 1.5μm, 1.8μm or 2μm. In addition, the composition of the hard carbon material can be, for example: 65wt% of the first hard carbon material 21, 30wt% of the second hard carbon material 22, 5wt% of the third hard carbon material, or 70wt% of the first hard carbon material 21, 25wt% of the second hard carbon material 22, 5wt% of the third hard carbon material, or 75wt% of the first hard carbon material 21, 10wt% of the second hard carbon material 22, 15wt% of the third hard carbon material, and so on.

[0056] Compared with the hard carbon material including only the first hard carbon material 21 and the second hard carbon material 22, by adding the third hard carbon material with Dv50 between the first hard carbon material 21 and the second hard carbon material 22, more gradation gradients can be provided, thereby further improving the filling effect of the gap space between adjacent first hard carbon materials 21 to ensure a higher degree of filling of the gap space.

[0057] Furthermore, Dn10 of the first hard carbon material 21 is 0.3 μm to 0.5 μm.

[0058] Furthermore, Dn10 of the second hard carbon material 22 is 0.3 μm to 0.5 μm.

[0059] Furthermore, Dn10 of the third hard carbon material is 0.45 μm to 0.55 μm.

[0060] When the Dn of each hard carbon material is preferably controlled within the above range, it is beneficial to further control the porosity of the negative electrode sheet within the scope of the application, thereby reducing the impact of the increased porosity on the compaction density of the negative electrode sheet.

[0061] It should be noted that in the embodiments of the present application, indicators such as Dv50, Dn10, cross-sectional area ratio in the active material layer 2, and average shape factor of each hard carbon material, as well as the porosity and compaction density of the negative electrode sheet can be determined by testing and calculation using methods or equipment known in the art.

[0062] For example, the microstructure and morphology of the hard carbon material can be analyzed by a particle size analyzer to obtain the particle size of the hard carbon material, and then obtain indicators such as Dv50 and Dn10; the cross-sectional area and cross-sectional circumference of the hard carbon material can also be calculated, and further calculated to obtain indicators such as the average shape factor and the porosity of the negative electrode sheet.

[0063] Preferably, the porosity of the negative electrode sheet is 4% to 6%. When the porosity of the negative electrode sheet is optimized within the range of 4% to 6%, especially when it is further optimized to 5%, the effect of improving the compaction density and the infiltration rate of the electrolyte to the active material layer 2 can be better balanced.

[0064] Furthermore, the compaction density of the negative electrode sheet is greater than or equal to 0.98 g / cm 3 . The present application found that with the effective improvement of the compaction density, not only the volume energy density of the battery is improved, but also the capacity retention rate is improved to a certain extent. It should also be noted that for the negative electrode sheet with graphite as the negative electrode active material, the interlayer interaction force of graphite is stronger, and it is easier to have a higher compaction density. However, for the scheme of the embodiment of the present application, it adopts a negative electrode sheet with hard carbon material as the main active material, and comprehensively regulates factors such as the particle size, cross-sectional proportion and porosity of different hard carbon materials to make the negative electrode sheet reach 0.98g / cm 3 The above compaction density is not easy to achieve.

[0065] Optionally, the first hard carbon material 21 and the second hard carbon material 22 are respectively prepared from precursors, and the precursors include one or more of a biomass-based precursor, a resin-based precursor, a pitch-based precursor, and a coal-based precursor.

[0066] Asphalt-based precursors or coal-based precursors have a high degree of carbonization and metamorphism, which is conducive to improving the compaction density of the hard carbon material obtained, but at the same time it also makes the hard carbon material obtained have too low capacity characteristics. The hard carbon material obtained by using biomass-based precursors or resin-based precursors has the characteristics of high capacity, but the compaction density is low, which will lead to a decrease in the volume energy density of the final battery.

[0067] In the embodiment of the present application, the precursor of the first hard carbon material 21 preferably adopts a biomass-based precursor or a resin-based precursor to obtain a higher capacity characteristic from the material properties; in particular, in the embodiment of the present application, the proportion of the first hard carbon material 21 is relatively high, which is more conducive to exerting its high capacity advantage. As for the compaction density, since the cross-sectional area of ​​the first hard carbon material 21 with a Dv50 of 4μm to 7μm in the embodiment of the present application accounts for 15% to 45% in the active material layer 2, and the second hard carbon material 22 with a smaller Dv50 is used to fill the gap space between adjacent first hard carbon materials 21, it is possible to increase the compaction density without affecting the capacity, thereby increasing the volume energy density of the battery.

[0068] In the second aspect, an embodiment of the present application provides a battery, comprising: a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the separator is arranged between the positive electrode plate and the negative electrode plate to form a battery cell, and the electrolyte is injected into the battery cell, wherein the negative electrode plate is the negative electrode plate as in the first aspect.

[0069] In a third aspect, an embodiment of the present application further provides an energy storage device 10, which includes the battery isolation membrane described in the first aspect or the second aspect.

[0070] Taking electrochemical energy storage as an example, an embodiment of the present application provides an energy storage device 10, which has a group of chemical batteries in it. The chemical elements in the batteries are mainly used as energy storage media. The charging and discharging process is accompanied by chemical reactions or changes in the energy storage media. In simple terms, the electricity generated by wind and solar energy is stored in chemical batteries. When the use of external electricity reaches a peak, the stored electricity is released for use, or transferred to places where electricity is scarce for use.

[0071] The current energy storage (i.e., energy storage) application scenarios are relatively wide, including energy storage on the power generation side, energy storage on the grid side, and energy storage on the power consumption side. The corresponding types of energy storage devices 10 include:

[0072] (1) Large-scale energy storage power stations applied to wind power and photovoltaic power stations can help renewable energy generation meet grid connection requirements and improve the utilization rate of renewable energy. As a high-quality active / reactive regulating power source on the power supply side, energy storage power stations can achieve load matching of electric energy in time and space, enhance the ability to absorb renewable energy, reduce instantaneous power changes, reduce the impact on the power grid, improve the absorption of new energy generation, and are of great significance in power grid system backup, relieving peak load power supply pressure, and peak and frequency regulation.

[0073] (2) Energy storage containers used on the grid side mainly perform peak load regulation, frequency regulation, and grid congestion relief. They can achieve peak load shaving and valley filling of power loads, that is, charging the energy storage batteries when the power load is low and releasing the stored power during the peak load period, thereby achieving a balance between power production and consumption;

[0074] (3) Small energy storage cabinets used on the power consumption side, the main functions are self-generation and self-use of electricity, peak-valley price difference arbitrage, capacity cost management and improving power supply reliability. According to different application scenarios, energy storage on the power consumption side can be divided into industrial and commercial energy storage cabinets, household energy storage devices 10, energy storage charging piles, etc., which are generally used in conjunction with distributed photovoltaics. Industrial and commercial users can use energy storage for valley-peak price difference arbitrage and capacity cost management. In the power market that implements peak-valley electricity prices, by charging the energy storage system 100 when the electricity price is low and discharging the energy storage system 100 when the electricity price is high, peak-valley electricity price difference arbitrage is achieved to reduce electricity costs. In addition, industrial enterprises that are subject to two-part electricity prices can use the energy storage system 100 to store energy during low electricity consumption and discharge it during peak load, thereby reducing peak power and the maximum demand reported, and achieving the purpose of reducing capacity electricity charges. Household photovoltaic storage can improve the level of self-generation and self-use of electricity. Due to high electricity prices and poor power supply stability, the demand for household photovoltaic installations is driven. Considering that photovoltaic power is generated during the day, and users generally have higher loads at night, energy storage can be configured to better utilize photovoltaic power, improve the level of self-generation and self-use, and reduce electricity costs. In addition, communication base stations, data centers and other fields need to configure energy storage for backup power.

[0075] See also Figure 5 , Figure 5 This is a structural diagram of a household energy storage system 100 of an embodiment of the present application. The present application provides a household energy storage system 100, which includes an electric energy conversion device 20 (photovoltaic panel), a first user load 30 (street lamp), a second user load 40 (such as air conditioners and other household appliances), and an energy storage device 10. The energy storage device 10 is a small energy storage box that can be mounted on an outdoor wall by wall hanging. Specifically, the photovoltaic panel can convert solar energy into electric energy during the period of low electricity prices. The energy storage device 10 is used to store the electric energy and supply it to street lamps and household appliances for use during peak electricity prices, or to supply power when the power grid is off / power outage.

[0076] See also Figure 6 , Figure 6 is a schematic diagram of the structure of an energy storage system 100 according to an embodiment of the present application, and the present application Figure 5 The embodiment is described by taking the shared energy storage scenario on the power generation / distribution side as an example, and the energy storage device 10 of the present application is not limited to the energy storage scenario on the power generation / distribution side.

[0077] The present application provides an energy storage system 100, which includes: a high-voltage cable 50, a first electric energy conversion device 60, a second electric energy conversion device 70 and an energy storage device 10 provided by the present application. In the case of power generation, the first electric energy conversion device 60 and the second electric energy conversion device 70 are used to convert other forms of energy into electric energy, connect with the high-voltage cable and supply it to the power distribution network for use. When the power load is low and the first electric energy conversion device 60 and the second electric energy conversion device 70 generate excess power, the excess power is stored in the energy storage device 10, reducing the wind and light abandonment rates and improving the problem of new energy power generation and consumption; when the power load is high, the power grid issues an instruction to use the power stored in the energy storage device 10 in conjunction with the high-voltage cable 50 to transmit the power to the power consumption side in a grid-connected mode, providing peak load regulation, frequency regulation, standby and other services for the operation of the power grid, giving full play to the peak load regulation of the power grid, promoting the peak load reduction and valley filling of the power grid, and alleviating the power supply pressure of the power grid.

[0078] Optionally, the first electric energy conversion device 60 and the second electric energy conversion device 70 can convert at least one of solar energy, light energy, wind energy, thermal energy, tidal energy, biomass energy and mechanical energy into electric energy.

[0079] The number of energy storage devices 10 can be multiple, and multiple energy storage devices 10 are connected in series or in parallel. Multiple energy storage devices 10 are supported and electrically connected by isolation plates (not shown). In this embodiment, "multiple" refers to two or more. An energy storage box can also be provided outside the energy storage device 10 to accommodate the energy storage device 10.

[0080] Optionally, the energy storage device 10 may include but is not limited to a battery module, a battery pack, a battery system, etc. The actual application form of the energy storage device 10 provided in the embodiment of the present application may be but is not limited to the listed products, and may also be other application forms. The embodiment of the present application does not strictly limit the application form of the energy storage device 10. The embodiment of the present application only takes the energy storage device 10 as a multi-core battery as an example for explanation. When the energy storage device 10 is a single battery, the energy storage device 10 may be at least one of a cylindrical battery, a square battery, etc.

[0081] The solution of the present application will be further introduced below in conjunction with specific embodiments and experimental data.

[0082] Example 1

[0083] This embodiment provides a negative electrode sheet, and the preparation method thereof comprises the following steps:

[0084] After weighing the spherical and quasi-spherical first hard carbon material and the three-dimensional geometric block-shaped second hard carbon material according to the mass ratio, they are put into a VC mixer for physical mixing, for example, running at a speed of 500 r / min for 2 hours until the hard carbon materials are completely mixed, thereby obtaining a negative electrode active material. The physical properties of the negative electrode active material are shown in Table 1 below.

[0085] The negative electrode active material, thickener carboxymethyl cellulose, conductive agent conductive carbon black, and binder styrene butadiene rubber are mixed in a mass ratio of 95:2:1.5:1.5, deionized water is added, and stirred evenly to obtain a negative electrode slurry with a solid content of 30%. The negative electrode slurry is evenly coated on one surface of the copper foil, and then vacuum dried, the negative electrode sheet is rolled and punched to obtain a circular negative electrode sheet.

[0086] Embodiment 2-3

[0087] Except for adjusting the first hard carbon material and the second hard carbon material according to the physical property parameters of the negative electrode active material in Table 1, the rest is the same as Example 1.

[0088] Embodiments 4 to 6

[0089] Except for adding the spherical and quasi-spherical third hard carbon material and adjusting the first hard carbon material and the second hard carbon material according to the physical property parameters of the negative electrode active material in Table 1, the rest is the same as Example 1.

[0090] Comparative Example 1

[0091] Except that the second hard carbon material is not used and the first hard carbon material and the second hard carbon material are adjusted according to the physical property parameters of the negative electrode active material in Table 1, the rest is the same as Example 1.

[0092] Comparative Example 2

[0093] Except for adjusting the first hard carbon material and the second hard carbon material according to the physical property parameters of the negative electrode active material in Table 1, the rest is the same as Example 1.

[0094] Comparative Examples 3-4

[0095] Except for adjusting the first hard carbon material and the second hard carbon material according to the physical properties of the negative electrode active material in Table 1, the rest is the same as Example 4.

[0096] <Battery Assembly>

[0097] Preparation of electrolyte: In an argon atmosphere glove box with a moisture content of ≤1ppm, ethylene carbonate and diethyl carbonate are mixed at a volume ratio of 1:1, and then sodium salt NaPF6 is added and dissolved in the above organic solvent, and the electrolyte is obtained after mixing evenly. The molar concentration of NaPF6 in the electrolyte is 1 mol / L.

[0098] Assembly of button cells: stack the circular sodium sheet, the diaphragm (glass fiber membrane with a thickness of 260 μm), and the circular negative electrode sheets of the above embodiments and comparative examples in order, so that the diaphragm is located between the circular sodium sheet and the negative electrode sheet to play an isolating role, and then inject the prepared electrolyte to assemble into a 2032-type button cell.

[0099] After the assembled button cell was left to rest for 12 hours, electrical performance tests such as charge and discharge tests were performed.

[0100] <Performance Test>

[0101] Hard carbon negative electrode material pole piece resistance test: The four-probe method is used to measure the current and voltage of the negative electrode using a resistivity tester, and then the resistivity under different pressures is calculated in Ω. The resistance data in Table 3 are all test results at a pressure of 25 MPa.

[0102] Cyclic performance test: The test temperature is 25°C. The button cells of the embodiment and the comparative example are discharged to 0.005V at 0.2C. After standing for 10 minutes, they are charged to 2V at 0.2C constant current. The capacity obtained in this step is the initial discharge capacity C0. The cycle test of 0.2C charge / 0.2C discharge is performed 200 times (circles), and the discharge capacity of the 200th cycle is recorded. Cyclic capacity retention rate = (discharge capacity of the 200th cycle / initial discharge capacity C0) × 100%.

[0103] Calculation of volume energy density: Battery volume energy density = battery capacity × discharge platform / volume. The basic unit is Wh / L (watt-hour / liter), where the battery capacity is 2.0V-4V capacity.

[0104]

[0105] Table 1 Physical properties of negative electrode active materials

[0106]

[0107] Table 2 Related parameters of negative electrode

[0108]

[0109] Table 3 Performance test results

[0110] It can be seen from Tables 1 to 3 above that the compaction density and cycle stability of Examples 1 to 6 are better than those of Comparative Example 1. It can be seen that the negative electrode sheets of the embodiments of the present application can indeed effectively improve the compaction density, thereby improving the volume energy density, and the cycle stability of the battery is also improved. Comparing Examples 1 to 6 with Comparative Example 2, it can be seen that although the cross-sectional area of ​​the first hard carbon material in Comparative Example 2 is relatively appropriate, the porosity of the negative electrode sheet of Comparative Example 2 is relatively high, which still leads to a decrease in compaction density, volume energy density, and cycle stability. Comparing Examples 1 to 6 with Comparative Example 4, it can be seen that although the porosity of the negative electrode sheet in Comparative Example 4 is relatively small, the cross-sectional area of ​​the first hard carbon material is too high, which still leads to a decrease in compaction density, volume energy density, and cycle stability.

[0111] By comparing Examples 1 to 3 with Examples 4 to 6, it can be seen that Examples 4 to 6 have better compaction density and cycle stability, indicating that the negative electrode active material uses the first hard carbon material, the second hard carbon material and the third hard carbon material of Dv50, which can further increase the compaction density to 1.02 g / cm 3 The above results show that the volume energy density and cycle stability can be improved more significantly. In particular, in Example 5, the compaction density is increased to 1.05 g / cm 3 higher level.

[0112] The battery isolation membrane and its preparation method and energy storage device disclosed in the embodiments of the present invention are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention: At the same time, for general technicians in this field, according to the ideas of the present invention, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present invention.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate comprises: current collector; An active material layer is disposed on the current collector; the active material layer comprises a first hard carbon material and a second hard carbon material, the Dv50 of the first hard carbon material is 4 μm to 7 μm, the Dv50 of the second hard carbon material is less than the Dv50 of the first hard carbon material, and the cross-sectional area of ​​the first hard carbon material in the active material layer accounts for 15% to 45%; The porosity of the negative electrode plate is 1% to 10%.

2. The negative electrode sheet according to claim 1, characterized in that: The first hard carbon material is at least one of spherical or quasi-spherical particles, the second hard carbon material is three-dimensional geometric block particles, and the Dv50 of the second hard carbon material is less than 4 μm.

3. The negative electrode sheet according to claim 2, characterized in that: The average shape factor F of the first hard carbon material is ≥ 0.75, and the average shape factor F = 4πA / P 2 , wherein A is the cross-sectional area of ​​the first hard carbon material, and P is the cross-sectional perimeter of the first hard carbon material.

4. The negative electrode sheet according to claim 2, characterized in that: In terms of mass percentage, the hard carbon material includes 60 wt % to 80 wt % of the first hard carbon material and 20 wt % to 40 wt % of the second hard carbon material; wherein the Dv50 of the second hard carbon material is 1.5 μm to 3 μm.

5. The negative electrode sheet according to claim 2, characterized in that: The hard carbon material further includes a third hard carbon material, the third hard carbon material is a spherical or quasi-spherical particle, and the Dv50 of the third hard carbon material is 2 μm to 4 μm; The Dv50 of the second hard carbon material is less than or equal to 2 μm; In terms of mass percentage, the hard carbon material includes 65 wt % to 75 wt % of the first hard carbon material, 10 wt % to 30 wt % of the second hard carbon material, and 5 wt % to 15 wt % of the third hard carbon material.

6. The negative electrode sheet according to claim 1, characterized in that: The Dn10 of the first hard carbon material is 0.3 μm to 0.5 μm; and / or, The Dn10 of the second hard carbon material is 0.3 μm to 0.5 μm; and / or, The active material layer further includes a third hard carbon material, and a Dn10 of the third hard carbon material is 0.45 μm to 0.55 μm.

7. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The porosity of the negative electrode sheet is 4% to 6%; and / or, The compaction density of the negative electrode plate is greater than or equal to 0.98 g / cm 3 .

8. The negative electrode sheet according to any one of claims 1 to 6, characterized in that: The first hard carbon material and the second hard carbon material are respectively prepared from precursors, and the precursors include one or more of a biomass-based precursor, a resin-based precursor, a pitch-based precursor, and a coal-based precursor.

9. A battery, characterized in that: The battery comprises: a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the separator is arranged between the positive electrode sheet and the negative electrode sheet to form a battery cell, and the electrolyte is injected into the battery cell, wherein the negative electrode sheet is the negative electrode sheet as described in any one of claims 1 to 8.

10. An energy storage device, characterized in that: The energy storage device comprises the negative electrode plate as described in any one of claims 1 to 8, or the energy storage device comprises the battery as described in claim 9.

Citation Information

Patent Citations

  • Battery cathode and lithium ion secondary battery comprising same

    CN101192662A

  • Negative electrode, and electrochemical device and electronic device including same

    CN113437252A

  • Negative electrode with particle size-pore dual gradient change and preparation method and application thereof

    CN116014125A

  • Hard carbon negative electrode material, hard carbon negative electrode plate and sodium ion secondary battery

    CN117374282A

  • Negative electrode sheet, secondary battery, battery module, battery pack, and electric apparatus

    WO2024011539A1

Cited By

  • Negative electrode sheet, battery, and energy storage device

    WO2026066442A1